Erosive Esophagitis in the Obese: The Effect of Ethnicity and Gender on Its Association - Albin Abraham; Seth Lipka; Rabab Hajar; Bhuma Krishnamachari; Ravi Virdi; Bobby Jacob; Prakash Viswanathan; Paul Mustacchia (Gastroenterology Research and Practice)
Background. Data examining the association between obesity and erosive esophagitis (ErE) have been inconsistent, with very little known about interracial variation. Goals. To examine the association between obesity and ErE among patients of different ethnic/racial backgrounds. Methods. The study sample included 2251 patients who underwent esophagogastroduodenoscopy (EGD). The effects of body mass index (BMI) on ErE were assessed by gender and in different ethnic groups. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using multivariate logistic regression analysis. Results. The prevalence of ErE was 29.4% (661/2251). Overweight and obese subjects were significantly more likely to have ErE than individuals with a normal BMI, with the highest risk seen in the morbidly obese (OR 6.26; 95% CI 3.82–10.28; p<0.0001). Normal weight Black patients were less likely to have ErE as compared to Caucasians (OR 0.46; 95% CI 0.27–0.79; p=0.005), while the odds ratio comparing normal weight Hispanics to normal weight Whites was not statistically significant. No effect modification was seen between BMI and race/ethnicity or BMI and gender. Significant trends were seen in each gender and ethnicity. Conclusions. The effect of BMI on ErE does not appear to vary by race/ethnicity or gender.